Analisis Jenis Zakat dan Instrumen Wakaf dalam Ekosistem Filantropi Islam - Abdullah Abbas; Alfiah Ariffianti; Dwi Hadi Suarno; Indah Lestari; Zico Al Fajri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Zakat and waqf represent Islamic financial instruments that equitably integrate two primary dimensions: a vertical theological aspect as a manifestation of a servant's obedience to the Creator, and a horizontal social aspect reflecting mutual care among fellow human beings. This study employs a qualitative approach using the library research method, wherein the analysis relies on the examination of texts, literature, and secondary data available across various print and digital media, independent of spatial and temporal constraints. In a macro context, the management of Islamic philanthropy in Indonesia has been accommodated by the state through formal legal regulations in the form of legislation, although regulatory overlaps are still frequently encountered in its practical implementation. This phenomenon of institutional intervention is highly compelling, as it shifts the governance paradigm from being predominantly centered on civil society to the formal realm of government administration. Through professional, transparent, and effective governance, zakat and waqf can transform into robust economic pillars capable of alleviating poverty, ensuring equitable wealth distribution, enhancing public welfare, and purifying the soul and wealth of the muzakki (almsgivers).